2008
DOI: 10.1016/j.ijgo.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnancies affected by hemoglobin H disease

Abstract: In spite of attempts to keep hemoglobin levels sufficiently high (>7.0 g/dL), pregnancies with HbH disease were significantly associated with increased risks of fetal growth restriction, preterm birth, and low birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
1
30
3
Order By: Relevance
“…Hydrop foetalis can be the outcome of pregnancy of mothers with Hb H disease,67–68 and in fact, according to a report on hydrop foetalis in Thailand by Taweevisit and Thorner (2008),69 3.8% were related to Hb H disease. Ong et al (1977)70 reported that Hb H disease probably had no adverse effect on pregnancy, although Tantiweerawong et al (2005)71 found that Hb H disease may adversely affect maternal and fetal health, causing in particular low birth weight.…”
Section: Delivery Outcomes Of Pregnancies and Breast-feedingmentioning
confidence: 99%
“…Hydrop foetalis can be the outcome of pregnancy of mothers with Hb H disease,67–68 and in fact, according to a report on hydrop foetalis in Thailand by Taweevisit and Thorner (2008),69 3.8% were related to Hb H disease. Ong et al (1977)70 reported that Hb H disease probably had no adverse effect on pregnancy, although Tantiweerawong et al (2005)71 found that Hb H disease may adversely affect maternal and fetal health, causing in particular low birth weight.…”
Section: Delivery Outcomes Of Pregnancies and Breast-feedingmentioning
confidence: 99%
“…Regarding the thalassemia disease in women, physiologic changes during pregnancy worsen the severity of anemia and are significantly associated with an increased risks of fetal growth restriction, preterm birth and low birthweight [ 3 5 ]. There are some reports on pregnancy outcomes among women with thalassemia trait [ 6 , 7 ], but, to our knowledge, no report on the risk of adverse pregnancy outcomes when compared with pregnant women without thalassemia trait has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy in HbH disease may be complicated mainly with anemia [12]. A study by Tongsong et al has shown that common obstetric complications such as antepartum hemorrhage, preeclampsia, and postpartum hemorrhage are not significantly associated with HbH disease [13] but Tantiweerawong et al have found that HbH may adversely affect maternal health [14]. …”
Section: Discussionmentioning
confidence: 99%
“…While a significant proportion of pregnancies in TI women was complicated by IUGR in a Lebanese study, blood transfusions during pregnancy do not seem to decrease the risk of IUGR as well as other complications [15]. On the contrary, Tongsong et al demonstrated that there are several benefits of frequent transfusions during pregnancy in HbH disease, like the prevention of growth restriction, suggesting that a strict control of hemoglobin levels could result in better outcome [13]. Data from nonthalassemic cohorts suggests that hemoglobin levels above 10 g/dL during gestation are recommended for optimal fetal growth and preclusion of preterm delivery [16].…”
Section: Discussionmentioning
confidence: 99%